2017
DOI: 10.3805/eands.9.18
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of epileptic encephalopathy after human herpesvirus 6-induced post-transplantation acute limbic encephalitis with adrenocorticotropic hormone therapy: A case report

Abstract: Recently, several authors have reported cases in which children with human herpesvirus 6-induced post-transplantation acute limbic encephalitis (HHV6-PALE) developed generalized epilepsy and cognitive deterioration. Here, we report an 8-year-old boy who developed HHV6-PALE one month after receiving cord blood transplant for precursor B lymphoblastic leukemia. At the age of 9 years, a series of epileptic spasms started, and his cognitive function deteriorated. An interictal electroencephalogram showed generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Notably, varied adverse events force termination of ACTH therapy 41 . Previous studies on long‐term therapy have not reported any severe adverse events 23–26,35 . However, we observed nonlethal adverse effects, including height stagnation, hypertension, and irritability.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Notably, varied adverse events force termination of ACTH therapy 41 . Previous studies on long‐term therapy have not reported any severe adverse events 23–26,35 . However, we observed nonlethal adverse effects, including height stagnation, hypertension, and irritability.…”
Section: Discussionmentioning
confidence: 58%
“…41 Previous studies on long-term therapy have not reported any severe adverse events. [23][24][25][26]35 However, we observed nonlethal adverse effects, including height stagnation, hypertension, and irritability. Clinicians who plan to initiate LT-ACTH should pay sufficient attention to these events, as well as give appropriate information to patients' caregivers.…”
Section: Adverse Events Of Lt-acthmentioning
confidence: 71%
See 2 more Smart Citations